Satellite On-board Processing of Synthetic Aperture Radar Data for Rapid Delivery of Latency Sensitive Maritime Information Products - Günzel, Dominik; Mandapati, Srikantha (Active and Passive Remote Sensing of Oceans, Seas, and Lakes, 2024)
In satellite remote sensing, there is usually a considerable delay between the time of acquisition and availability of usable images, and even more time passes until derived products can be delivered to relevant stakeholders. For certain applications though, latency is critical as the contained information decays rapidly. A promising solution to achieving faster product delivery is breaking up the existing paradigm by moving data processing on-board of the satellite. This presentation provides an overview of our developments regarding satellite on-board processing of Synthetic Aperture Radar (SAR) data, focusing in particular on products concerning maritime safety and security including artificial intelligence, such as ship location, ocean wave height, and sea ice classification